Psychosocial Support Provided by Health Volunteer for Older Adult with Depression and Suicide Attempt: A Case Study - AEKWARANGKOON, Saifon; NOONIL, Naiyana; PETSIRASAN, Rewwadee (Walailak Journal of Science and Technology (WJST), 2018)
Depression causes major disabilities and can lead to suicide among older adults in Thai rural communities. A case study was used to present the psychosocial support provided by a health volunteer to an older adult suffering from depression and attempted suicide. Content analysis was applied to analyze the data. The results revealed that the psychosocial support given by the health volunteer consisted of 4 processes; 1) support and motivation to keep alive, 2) encouragement for a new life, 3) empowerment for life change, and 4) evaluation of the change process. These processes not only help mitigate patients’ symptoms of depression and possible suicide risks but also prove to promote psychological well-being. The patient outcome benefits indicated sustainability over the course of 18 months.